Reintroduction of DJ-1 in Müller Cells Inhibits Retinal Degeneration in the DJ-1 Deficient Retina - Naouel Gharbi; Dagne Røise; Jorunn-Elise Førre; Amanda J. Edson; Helena A. Hushagen; Valentina Tronci; Ann-Kristin Frøyset; Kari E. Fladmark (MDPI AG, 2021)
The eye is continuously under oxidative stress due to high metabolic activity and reactive oxygen species generated by daily light exposure. The redox-sensitive protein DJ-1 has proven to be essential in order to protect retina and retinal pigment epithelium (RPE) from oxidative-stress-induced degeneration. Here, we analyzed the specific role of Müller cell DJ-1 in the adult zebrafish retina by re-establishing Müller-cell-specific DJ-1 expression in a DJ-1 knockout retina. Loss of DJ-1 resulted in an age-dependent retinal degeneration, including loss of cells in the ganglion cell layer, retinal thinning, photoreceptor disorganization and RPE cell dysfunction. The degenerative phenotype induced by the absence of DJ-1 was inhibited by solely expressing DJ-1 in Müller cells. The protective effect was dependent upon the cysteine-106 residue of DJ-1, which has been shown to be an oxidative sensor of DJ-1. In a label-free proteomics analysis of isolated retinas, we identified proteins differentially expressed after DJ-1 knockout, but with restored levels after Müller cell DJ-1 re-insertion. Our data show that Müller cell DJ-1 has a major role in protecting the retina from age-dependent oxidative stress.